Building a Climate-Resilient Power Grid: Lessons From Texas-Size Storms and the Queensland Floods - Verchick, Robert R. M.; Lyster, Rosemary (Frontiers in Climate, 2021)
When a city is lashed by storm or swamped by epic rains, there's at least one predictable moment in the chaos: the lights go out. In this article, we focus on the challenge of protecting assets from storms and floods in the era of climate breakdown. This often involves physical fortification or smarter placement. To understand the policies and decisions involved, we examine recovery efforts following storm- or flood-based outages that occurred this century in the state of Texas in the United States and the state of Queensland in Australia. We first describe the outages, their consequences, and the policy recommendations and responses that followed. We then evaluate the recovery processes, focusing on the challenge of protecting assets like substations and transmission structures. We find that each jurisdiction could do more to incorporate forward-looking climate data, to match the level of government authority to better fit the desired function, and to capably fund the work to be done.